2024
DOI: 10.1001/jamaneurol.2023.5716
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Edaravone Dexborneol for the Treatment of Acute Ischemic Stroke

Yu Fu,
Anxin Wang,
Renhong Tang
et al.

Abstract: ImportanceSublingual edaravone dexborneol, which can rapidly diffuse and be absorbed through the oral mucosa after sublingual exposure, is a multitarget brain cytoprotection composed of antioxidant and anti-inflammatory ingredients edaravone and dexborneol.ObjectiveTo investigate the efficacy and safety of sublingual edaravone dexborneol on 90-day functional outcome in patients with acute ischemic stroke (AIS).Design, Setting, and ParticipantsThis was a double-blind, placebo-controlled, multicenter, parallel-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The Treatment of Acute Ischemic Stroke with Edaravone Dexborneol (TASTE) trial, a phase III, randomized, double-blind, parallel, comparative study, enrolled 1200 participants with AIS, which has reported an effective neuroprotective agent of edaravone dexborneol in the improvement of 90-day functional outcomes [ 9 ]. Furthermore, the following TASTE-SL trial also showed sublingual edaravone dexborneol achieved a favorable outcome at 90 days in patients with AIS within 48 h [ 10 ]. Previous studies have highlighted its involvement in inhibiting pro-inflammatory factors and enhancing blood-brain barrier permeability following ischemic stroke [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Treatment of Acute Ischemic Stroke with Edaravone Dexborneol (TASTE) trial, a phase III, randomized, double-blind, parallel, comparative study, enrolled 1200 participants with AIS, which has reported an effective neuroprotective agent of edaravone dexborneol in the improvement of 90-day functional outcomes [ 9 ]. Furthermore, the following TASTE-SL trial also showed sublingual edaravone dexborneol achieved a favorable outcome at 90 days in patients with AIS within 48 h [ 10 ]. Previous studies have highlighted its involvement in inhibiting pro-inflammatory factors and enhancing blood-brain barrier permeability following ischemic stroke [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%